Per-arnt-sim (PAS) domain-containing protein kinase is downregulated in human islets in type 2 diabetes and regulates glucagon secretion. - da Silva Xavier, G; Farhan, H; Kim, H; Caxaria, S; Johnson, P; Hughes, S; Bugliani, M; Marselli, L; Marchetti, P; Birzele, F; Sun, G; Scharfmann, R; et al. (2011)
AIMS/HYPOTHESIS: We assessed whether per-arnt-sim (PAS) domain-containing protein kinase (PASK) is involved in the regulation of glucagon secretion. METHODS: mRNA levels were measured in islets by quantitative PCR and in pancreatic beta cells obtained by laser capture microdissection. Glucose tolerance, plasma hormone levels and islet hormone secretion were analysed in C57BL/6 Pask homozygote knockout mice (Pask-/-) and control littermates. Alpha-TC1-9 cells, human islets or cultured E13.5 rat pancreatic epithelia were transduced with anti-Pask or control small interfering RNAs, or with adenoviruses encoding enhanced green fluorescent protein or PASK. RESULTS: PASK expression was significantly lower in islets from human type 2 diabetic than control participants. PASK mRNA was present in alpha and beta cells from mouse islets. In Pask-/- mice, fasted blood glucose and plasma glucagon levels were 25 ± 5% and 50 ± 8% (mean ± SE) higher, respectively, than in control mice. At inhibitory glucose concentrations (10 mmol/l), islets from Pask-/- mice secreted 2.04 ± 0.2-fold (p < 0.01) more glucagon and 2.63 ± 0.3-fold (p < 0.01) less insulin than wild-type islets. Glucose failed to inhibit glucagon secretion from PASK-depleted alpha-TC1-9 cells, whereas PASK overexpression inhibited glucagon secretion from these cells and human islets. Extracellular insulin (20 nmol/l) inhibited glucagon secretion from control and PASK-deficient alpha-TC1-9 cells. PASK-depleted alpha-TC1-9 cells and pancreatic embryonic explants displayed increased expression of the preproglucagon (Gcg) and AMP-activated protein kinase (AMPK)-alpha2 (Prkaa2) genes, implying a possible role for AMPK-alpha2 downstream of PASK in the control of glucagon gene expression and release. CONCLUSIONS/INTERPRETATION: PASK is involved in the regulation of glucagon secretion by glucose and may be a useful target for the treatment of type 2 diabetes.